Potential of predatory mites for biological control of Brevipalpus yothersi (Acari: Tenuipalpidae) - Argolo, Poliane S.; Revynthi, Alexandra M.; Canon, Maria A.; M. Berto, Marielle; Andrade, Daniel Junior [UNESP]; Döker, İsmail; Roda, Amy; Carrillo, Daniel (Elsevier, 2020)
Citrus leprosis is a serious viral disease of citrus transmitted by Brevipalpus mites. The disease is present in South America, Central America, and Mexico, but not in the United States. One of its primary vectors, however, is present in Florida and other southern states. Non-viruliferous Brevipalpus yothersi (Acari: Tenuipalpidae) are present in Florida and could facilitate the spread of the disease if citrus leprosis viruses (CiLVs) are introduced into the state. In preparation for the possible incursion of CiLVs, we evaluated the biological control potential of four predatory mite species (Neoseiulus longispinosus, N. californicus, Amblyseius largoensis; Acari: Phytoseiidae) and Hemicheyletia bakeri (Acari: Cheyletidae) that are naturally associated with Brevipalpus spp. in citrus. In laboratory no-choice assays, the phytoseiid mites preyed mostly upon immature stages of B. yothersi, while H. bakeri preyed mainly on adults. In dual choice assays, all predators preferred Tetranychus urticae (Acari: Tetranychidae) over B. yothersi, but A. largoensis consumed more B. yothersi than the other three predators. A greenhouse experiment was performed to evaluate the potential of A. largoensis and H. bakeri to suppress B. yothersi populations on citrus trees. Four predator release treatments consisting of single or combined releases of A. largoensis and H. bakeri at a 1:10 (predator: B. yothersi) ratio were tested. Releases of A. largoensis alone or in combination with H. bakeri effectively suppressed B. yothersi and reduced damage to citrus plants. Release of H. bakeri alone, however, had no suppressive effect on B. yothersi populations. Overall, our results show that A. largoensis could be an efficient biological control agent of B. yothersi and could play an important role in citrus IPM programs tailored to manage citrus leprosis.
Keywords: Cheyletidae; Citrus leprosis; Flat mite; Natural enemies; Phytoseiidae